Numerical Investigation on Multiphase Flows in Various Configurations of Microchannels Using Computational Fluid Dynamics - Majnis, Mohd Fadhil; Jalwan, Mohamad Rawad (ASEAN Journal of Chemical Engineering, 2017)
A two-dimensional domain of multiphase flow analyses in this study using the Volume of Fluid (VOF) model was carried out in order to simulate and predict the fluid flows and mixing performance of two miscible liquids in various microchannel configurations. The various microchannels configurations were designed accordingly and the simulation was carried out based on the justified conditions, assumptions and considerations by using the commercial computational fluid dynamics (CFD) software, FLUENT. The grid type and size of the computational domain were verified in terms of stability by performing the grid independence analysis. The result showed that static mixing would be possible to achieve in various configurations of microchannels, however, the simulation results predicted that it appeared to be more efficient in complex and retrofitted microchannels. It showed the potential to promote and enhance chaotic advection, compositions distribution, and diffusivity as compared to basic microchannels that are mostly dependent only on the injection focus. Furthermore, the Reynolds number appeared to be a significant factor to enhance the mixing performance in microchannel beside the configurations.